Comparative study of cervical cytology in HIV-infected and non-HIV-infected women - Devani, Shruti D.; Tailor, Tanvi; Jivani, Toral B.; Jivani, Kiah B. (International Journal of Research in Medical Sciences, 2025)
Background: Cervical cancer remains a major preventable cause of morbidity and mortality among women worldwide, with HIV-infected women demonstrating a substantially higher susceptibility to persistent HPV infection and cervical dysplasia. This study compares cervical cytological findings in HIV-positive and HIV-negative women using Pap smear screening. Methods: A six-month retrospective study was conducted on 200 Pap smears (100 HIV-positive, 100 HIV-negative) reported according to the 2014 Bethesda System. Unsatisfactory smears were excluded and cytological patterns were analyzed and compared. Results: HIV-positive women showed a markedly higher prevalence of cervical abnormalities. Squamous epithelial abnormalities (SEA) were observed in 17% of HIV-positive women compared to 5% of HIV-negative women. Non-squamous abnormalities, including infectious etiologies such as bacterial vaginosis, candidiasis and trichomonas, were also significantly higher in the HIV-positive cohort (34% vs 12%). NILM rates were substantially lower among HIV-infected women (49% vs 79%). Conclusions: HIV infection is strongly associated with increased cervical cytological abnormalities, underscoring the need for early, routine and targeted cervical screening, including Pap and HPV testing, in HIV-positive women to enable timely intervention and reduce the risk of cervical cancer.